ALASAN PENUTUPAN THE KING ABDULLAH BIN ABDULAZIZ INTERNATIONAL CENTRE FOR INTERRELIGIOUS AND INTERCULTURAL DIALOGUE (KAICIID) OLEH PEMERINTAH AUSTRIA TAHUN 2019 - Dra. Harmiyati; Muwalliha Syahdani (Jurusan Ilmu Hubungan Internasional, 2022)
This article discusses the closure of The King Abdullah bin Abdulaziz International Centre for Interreligious and Intercultural Dialogue (KAICIID) by the Government of Austria (GoA) in 2019. This article also discusses the background of the establishment of KAICIID first which has been initiated since 2008, primarily when King Saud of Saudi Arabia came to the Vatican. To explain the closure, this article will see the development of Islamophobia intensity in the domestic sphere of Austria. This factor becomes the most notable factor in the decision-making process of GoA in closing the KAICIID. Apart from the three actions of external factor which has been done by the Government of Saudi Arabia in seeing the closure of KAICIID in Austria.